2005
DOI: 10.1016/j.orthres.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit knee joint biomechanics: Motion analysis and modeling of forces during hopping

Abstract: Although the rabbit hindlimb has been commonly used as an experimental animal model for studies of osteoarthritis, bone growth and fracture healing, the in vivo biomechanics of the rabbit knee joint have not been quantified. The purpose of this study was to investigate the kinematic and kinetic patterns during hopping of the adult rabbit, and to develop a model to estimate the joint contact force distribution between the tibia1 plateaus. Force platform data and three-dimensional motion analysis using infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
2
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 34 publications
9
78
2
1
Order By: Relevance
“…23 Both load levels used in our study were well above the normal loading experienced at that anatomical location in the rabbit; therefore, normal loading likely did not contribute to our finding that load but not load magnitude had an influence on trabecular bone mass, density, or architecture. 24,25 Similar to our results, other studies examining load levels above those involved in normal loading also observed an anabolic response in trabecular bone and did not see an effect of different load magnitudes on bone mass, suggesting a threshold response to loading. A previous study examining the response of trabecular bone to noninvasive axial compressive loading found no effects of load level (8,10, or 12 N) on trabecular microCT parameters in 7-or 22-month-old male BALB/c mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…23 Both load levels used in our study were well above the normal loading experienced at that anatomical location in the rabbit; therefore, normal loading likely did not contribute to our finding that load but not load magnitude had an influence on trabecular bone mass, density, or architecture. 24,25 Similar to our results, other studies examining load levels above those involved in normal loading also observed an anabolic response in trabecular bone and did not see an effect of different load magnitudes on bone mass, suggesting a threshold response to loading. A previous study examining the response of trabecular bone to noninvasive axial compressive loading found no effects of load level (8,10, or 12 N) on trabecular microCT parameters in 7-or 22-month-old male BALB/c mice.…”
Section: Discussionsupporting
confidence: 90%
“…Both load levels were well above the normal loading experienced at that anatomical location in the rabbit. 24,25 In addition, the loading in this model is applied in a direction that is not habitually loaded in vivo: perpendicular to the lateral surface of the condyle. Control of cortical bone remodeling has been hypothesized to be dominated by error signals from loading situations to which the bone was not habituated.…”
Section: Discussionmentioning
confidence: 99%
“…muscular activity. The compression forces acting on the rabbit knee have been estimated to be about three times bodyweight when hopping, 29 implying a stress at the growth plate of about 0.5 MPa. The mean ultimate tensile stress of 5-month-old bovine growth plates was reported as 1.4 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…36 Stair climbing results in larger relative bending moments than walking, so animals with flexed joints might also have higher amounts of bending moments in their femora. One study characterized knee biomechanics in rabbits, 41 providing insight in the differences in relative forces and moments compared to larger animals. From that study it can be anticipated that there would be larger bending moments on the femora in small animals such as mice.…”
Section: Remodeling Of Fracture Callus In Micementioning
confidence: 99%